2004
DOI: 10.1016/j.ejvs.2003.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Varicose Veins after Surgery: A New Appraisal of a Common and Complex Problem in Vascular Surgery

Abstract: This study shows that the recurrence of varicose veins after surgery is not uncommon. However, the clinical condition of most affected limbs remains improved. Progression of the disease and neovascularisation are responsible for more than half of the recurrences. Rigorous evaluation of patients and assiduous surgical technique might reduce recurrence due to technical and tactical failures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
115
3
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(135 citation statements)
references
References 30 publications
3
115
3
7
Order By: Relevance
“…At 2 years follow-up, a recurrence rate of 16% was demonstrated by clinical and Duplex evaluation in a study by Coufinhal [18] The rate of disease recurrence increases with time, probably because of progression of the disease. Kostas et al identified three main causes of disease recurrence [19]. The first was attributable to inadequate initial treatment and results in recurrence in 55-70% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…At 2 years follow-up, a recurrence rate of 16% was demonstrated by clinical and Duplex evaluation in a study by Coufinhal [18] The rate of disease recurrence increases with time, probably because of progression of the disease. Kostas et al identified three main causes of disease recurrence [19]. The first was attributable to inadequate initial treatment and results in recurrence in 55-70% of cases.…”
Section: Discussionmentioning
confidence: 99%
“…The reported rate of clinical recurrence ranges from 20 to 80% after a period between 5 and 20 years [15]. The average time between the first and the second surgical treatments is long ranging, from 6 to 20 years [16,17].…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence can refer to either clinical recurrence (ie, varicose vein recurrence) or hemodynamic recurrence (ie, SFJ reflux). Varicose vein recurrence rates after vein stripping have been reported between 20% and 50% at 2 to 5 years [34][35][36][37][38][39][40][41] and up to 70% by 10 years [42]. The varicose vein recurrence rate is more subjective; the recurrence of SFJ reflux is a more objective measure and provides important hemodynamic information that permits detection and prediction of clinical recurrence.…”
Section: Endovenous Radiofrequency Ablation Versus Vein Strippingmentioning
confidence: 99%
“…С одной стороны, частота рецидива может показаться высокой, но в литературе содержатся многочисленные указания на то, что вероятность рецидива при традиционном подходе не меньше по лученных нами данных. При сроке наблюдения 3-5 лет рецидив происходит в 15-20% случаев вне зависимости от использованного хирургического метода [10][11][12][13][14][15][16]. L. Rassmussen и соавт.…”
Section: Discussionunclassified